Two new oleanane-type saponins from Elaeocarpus hainanensis Oliv. growing in Vietnam. (October 2018) - Nga, Dao Thu; Duong, Pham Quang; Le Dang, Quang; Tung, Nguyen Huu; Hoang, Vu Dinh
Graphical abstract: Highlights: Two new oleanane-type saponins were isolated from Elaeocarpus hainanensis . The structural elucidation was based on their chemical and spectroscopic analyses. This is the first report on oleanane-type saponins in the genus Elaeocarpus . The presence of triterpene saponins in E. hainanensis has chemotaxonomical meaning. Abstract: Two new oleanane-type saponins, 1 α- hydroxy-olean-12-en-3- O - β -D-xylopyranoside (1 ) and 1 α- hydroxy-olean-12-en-3- O - α -L-arabinopyranoside (2 ), along with six known compounds (3 -8 ), were isolated from the leaves and twigs of Elaeocarpus hainanensis Oliv. Their structures were determined based on chemical and spectroscopic analyses. This is the first report on oleanane-type triterpenoids in the genus Elaeocarpus .